Paste

CN120826447APending Publication Date: 2025-10-21NIPPON VALQUA IND LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480016861.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-16
Filing Date
2024-02-21
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing pastes have low viscosity during coating, which leads to overflow and makes it difficult to maintain effective heat transfer between the heating element and the heat dissipation component for a long time. In addition, existing curing methods increase the complexity and cost of the production process.

Method used

An anaerobic paste is used, containing a thiol-containing polysiloxane and a redox initiator. It thickens at room temperature when in contact with metal parts and isolated from air. It crosslinks by forming free radicals through redox reactions, preventing overflow and increasing flow resistance.

Benefits of technology

Anaerobic paste thickens quickly, inhibits overflow, maintains excellent heat dissipation performance, and simplifies the production process without the need for heating or light exposure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005580989630000071
    Figure BDA0005580989630000071
  • Figure BDA0005580989630000141
    Figure BDA0005580989630000141
  • Figure BDA0005580989630000241
    Figure BDA0005580989630000241
Patent Text Reader

Abstract

An anaerobic paste which contains a polysiloxane (A) having a mercapto group and a redox initiator (B), is tackified at room temperature under anaerobic conditions while being in contact with a metal member, and is in the form of a paste or a rubber after tackifying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to a paste. Background Art

[0002] In components such as sliding components, brake components, and vibration suppression and absorption components, paste (also called a paste) is used between components to ensure their predetermined motion, wear resistance, and seizure resistance.

[0003] Furthermore, heat dissipation (thermal conductivity) materials are used between the heat generating element of electronic components and the heat dissipation components to effectively transfer the heat generated by the heat generating element to the heat dissipation components. In recent years, with the miniaturization and higher output of electronic components such as power modules, the amount of heat generated per unit area by these electronic components has become extremely large. To ensure the normal operation and long-term reliability of electronic components, heat dissipation materials with excellent heat dissipation properties are required.

[0004] There are two main forms of heat dissipation materials: sheet and paste. However, sheet materials have poor adhesion to the target surface, such as the heating element or heat dissipation component, and require a certain thickness, resulting in increased thermal resistance. Therefore, paste materials are used due to their ability to be thinner, good adhesion to the target surface, and excellent heat dissipation performance.

[0005] If the viscosity of the paste during application is low, workability and productivity, such as coating efficiency, are improved, making it easier to apply a specific amount, especially a small amount, of paste to a specific location. For example, in the case of the heat dissipation material, the thickness of the paste layer can be reduced, which can improve heat dissipation performance, so a low viscosity during application is required.

[0006] On the other hand, in order to achieve the desired purpose of the paste, the paste is also required to remain in a specified location (for example, between the heating element and the heat dissipation component). However, since the viscosity of the paste is low when it is applied, the flow resistance is low. Therefore, there is a problem of so-called overflow in which the paste is discharged from the specified location due to the heat cycle applied to the electronic components, etc., and it is difficult to maintain long-term heat dissipation performance.

[0007] To address this issue, a method has been proposed for heat dissipation pastes using silicone-based materials as their base oil, using a platinum catalyst addition reaction to lower viscosity during application, followed by curing of the base oil after application to increase flow resistance and prevent bleeding (Patent Document 1). Other methods have also been proposed, such as curing by ultraviolet irradiation using a photoactive platinum complex curing catalyst (Patent Document 2) and curing by heating using an organic peroxide (Patent Document 3). Prior art literature Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2017-75282 Patent Document 2: Japanese Patent Application Laid-Open No. 2016-089127 Patent Document 3: Japanese Patent Application Laid-Open No. 2017-226724 Summary of the Invention

[0009] For example, the addition reaction-type compositions described in Patent Document 1 and the like include one-component and two-component compositions. However, considering operational ease such as tedious mixing, one-component compositions are preferred, and Patent Document 1 also describes a one-component composition. However, the one-component compositions described in Patent Document 1 and the like must be stored frozen or refrigerated, making storage and management of such compositions difficult.

[0010] Furthermore, the UV irradiation type and heat curing type require UV irradiation and heating steps for curing, respectively. Therefore, these steps need to be integrated into the production process of electronic components, etc. This makes the process complicated and the production time lengthened, thereby reducing production efficiency.

[0011] One embodiment of the present invention provides an anaerobic paste that, despite having a low initial viscosity, increases in viscosity at room temperature (remains in a paste or rubbery state without curing) when in contact with a metal part and isolated from air (anaerobic conditions), thereby preventing overflow. Here, the initial viscosity refers to the viscosity when the anaerobic paste is prepared, and is the viscosity before the anaerobic paste is thickened, and is generally the viscosity during coating. Means of solving technical problems

[0012] The configuration examples of the present invention are as follows.

[0013] [1] An anaerobic paste comprising a polysiloxane having a mercapto group (A) and a redox initiator (B), It thickens under anaerobic conditions at room temperature when in contact with metal parts, and becomes paste-like or rubber-like after the thickening.

[0014] [2] The anaerobic paste according to [1], wherein the initial shear viscosity at 23°C is 500 Pa·s or less.

[0015] [3] The anaerobic paste according to [1] or [2], wherein the functional group ratio represented by the following formula (1) is 1.0×10 -3 the following. Functional group ratio = (the amount of the polysiloxane (A) blended / the functional group equivalent of the polysiloxane (A)) × (the amount of the redox initiator (B) blended / the active oxygen equivalent of the redox initiator (B)) ... (1)

[0016] [4] The anaerobic paste according to any one of [1] to [3], further comprising a thermally conductive filler (D).

[0017] [5] The anaerobic paste according to [4], wherein the content of the thermally conductive filler (D) is 30 to 80% by volume relative to 100% by volume of the anaerobic paste. Effects of the Invention

[0018] According to one embodiment of the present invention, an anaerobic paste can be provided that, despite having a low initial viscosity, increases in viscosity at room temperature (remains in a paste or rubbery state without solidifying) when in contact with a metal component and isolated from air (oxygen) (anaerobic conditions), thereby suppressing overflow. Specifically, simply by placing the anaerobic paste according to one embodiment of the present invention between, for example, a heating element and a heat dissipation component (where at least one of the components in contact with the anaerobic paste is a metal component) and compressing them (isolated from oxygen), the paste increases in viscosity and increases in flow resistance in a short period of time without the need for heating or light irradiation, thereby suppressing overflow. Furthermore, according to one embodiment of the present invention, an anaerobic heat dissipation paste having excellent heat dissipation performance can also be provided. DETAILED DESCRIPTION

[0019] Anaerobic paste The anaerobic paste according to one embodiment of the present invention (hereinafter also referred to as "this paste") comprises a polysiloxane (A) having a mercapto group [hereinafter also referred to as "component (A)", the same applies to other components] and a redox initiator (B). The viscosity is increased at room temperature under anaerobic conditions while in contact with a metal member (hereinafter also referred to as "anaerobic room-temperature viscosity increase"), and the viscosity is in a paste or rubber state after the anaerobic room-temperature viscosity increase.

[0020] By placing the paste between, for example, a heating element and a heat dissipating component (where at least one of the components in contact with the anaerobic paste is a metal component) and compressing the component (to isolate oxygen), oxygen is isolated. Furthermore, it is believed that the catalytic effect of metal ions or mercapto groups from the metal component causes the redox initiator to cleave, generating free radicals. The generated free radicals extract protons from the mercapto groups, causing a cross-linking reaction and increasing the viscosity of the paste. Therefore, when using the paste, the paste can be thickened in a short time and in a simplified process without conventionally required steps (such as heating and light irradiation), thereby suppressing overflow and maintaining long-term performance (such as heat dissipation).

[0021] In the present invention, the term "paste" means a paste having a thickness of 200 μm or less when 0.2 g of the paste is formed into a 5 mm square and then compressed at 23° C. and 1.0 MPa. The method for measuring the thickness is specifically described in the examples below.

[0022] In the present invention, the term "rubber" is defined as having elasticity rather than being pasty, and having a surface Martens hardness of 10 N / mm2 as measured by an ultra-microhardness tester using a triangular pyramid indenter (edge ​​angle 115°) with a maximum test force of 0.3 mN. 2 the following. In the present invention, "cured" is defined as a state that is neither pasty nor rubbery, and the surface Martens hardness measured by an ultra-microhardness tester with a triangular pyramid indenter (edge ​​angle 115°) as the measuring indenter is greater than 10 N / mm with a maximum test force of 0.3 mN. 2 .

[0023] The paste does not solidify even after anaerobic viscosity-increasing at room temperature, and is in a paste or rubber state after anaerobic viscosity-increasing at room temperature. After the present paste is thickened at room temperature under conditions of contact with metal parts and under anaerobic conditions, specifically, 4 g of the present paste is clamped between two copper plates at 23°C and compressed for 2.5 hours until the thickness of the paste reaches 0.4 mm, and then 0.2 g of the compressed body is made into a 5 mm square and compressed at a pressure of 1.0 MPa at 23°C to a thickness of less than 200 μm, or the surface Martens hardness of the compressed body is measured by an ultra-micro hardness tester using a triangular pyramid indenter (edge ​​angle 115°) as a measuring indenter with a maximum test force of 0.3 mN to be 10 N / mm 2 the following. The method for measuring the thickness is specifically described in the examples below.

[0024] In the present invention, "thickening" means that the viscosity after anaerobic and room-temperature thickening is increased by at least 10% compared to the initial viscosity.

[0025] The present paste may be a two-component (e.g., two-liquid) or higher composition comprising a first agent containing component (A) and a second agent containing component (B), but is preferably a one-component (e.g., one-liquid) composition in consideration of operability such as complicated mixing.

[0026] <Polysiloxane (A)> Component (A) is not particularly limited as long as it is a polysiloxane having a mercapto group (—SH). Component (A) may also have a functional group other than a mercapto group (e.g., a group having an ethylenically unsaturated bond [e.g., a vinyl group, a (meth)acryloyl group]). By using such a component (A), excellent heat resistance is achieved, and the composition does not solidify even after anaerobic thickening at room temperature, and a paste-like or rubber-like paste can be easily obtained after anaerobic thickening at room temperature. The component (A) used in the present paste may be one kind or two or more kinds.

[0027] The bonding position of the mercapto group is not particularly limited and may be a so-called side chain type, a terminal type (including a single terminal type and a double terminal type), or a side chain double terminal type. However, the side chain type or the double terminal type is preferred, and the side chain type is more preferred.

[0028] As component (A), an organopolysiloxane in which an organic group is bonded to a silicon atom, and a polysiloxane having a mercapto group in at least a portion of the organopolysiloxane is preferred.

[0029] Examples of the organic group bonded to a silicon atom include a linear alkyl group, a branched alkyl group, a cyclic alkyl group, an aryl group, an aralkyl group, a halogenated alkyl group and an alkoxy group. Examples of the linear alkyl group include a group having 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms, such as a methyl group, an ethyl group, a propyl group, a hexyl group, an octyl group, and a decyl group. Examples of the branched alkyl group include an isopropyl group, an isobutyl group, a tert-butyl group, a 2-ethylhexyl group, and a group having 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms. Examples of the cyclic alkyl group include groups having 3 to 20 carbon atoms, such as cyclopentyl and cyclohexyl. Examples of the aryl group include groups having 6 to 20 carbon atoms, such as a phenyl group and a tolyl group. Examples of the aralkyl group include groups having 7 to 20 carbon atoms, such as benzyl, 2-phenylethyl and 2-methyl-2-phenylethyl. Examples of the haloalkyl group include a group having 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms, such as 3,3,3-trifluoropropyl, 2-(nonafluorobutyl)ethyl, and 2-(heptadecafluorooctyl)ethyl. Examples of the alkoxy group include groups having 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms, such as a methoxy group and an ethoxy group.

[0030] As the organic group bonded to the silicon atom, a linear alkyl group or an aryl group is preferred, a linear alkyl group or an aryl group having 1 to 6 carbon atoms is more preferred, and a methyl group or a phenyl group is particularly preferred. Specifically, as a structure other than the portion having a mercapto group in the organopolysiloxane, it is preferred that the organopolysiloxane have at least one polysiloxane structure selected from dimethylpolysiloxane, methylphenylpolysiloxane, and diphenylpolysiloxane, and more preferably a dimethylpolysiloxane structure.

[0031] The mercapto group may be directly bonded to the silicon atom or may be bonded to the silicon atom via an organic group bonded to the silicon atom.

[0032] The molecular structure of component (A) is not particularly limited, and examples thereof include linear, branched, linear with some branches, and dendrimer-like structures. Linear and linear with some branches are preferred. Component (A) can be a homopolymer having these molecular structures, a copolymer having these molecular structures, or a mixture of two or more of these polymers.

[0033] As component (A), specifically, the polysiloxane represented by the following formula (2) can be exemplified.

[0034] [Chemical 1] [In formula (2), R 1 and R 2 are each independently an unsubstituted or substituted monovalent hydrocarbon group, a mercapto group, an alkoxy group, or -R-SH (R is a hydrocarbon group having 1 to 20 carbon atoms), and the sum of a and b is an integer of 2 to 500. Among them, at least one of R 1 and R 2 in formula (2) contains a mercapto group or -R-SH, and the plurality of R 1 present in formula (2) may be the same or different from each other, and the plurality of R 2 present in formula (2) may be the same or different from each other.]

[0035] As the unsubstituted or substituted monovalent hydrocarbon group in R 1 and R 2 , an unsubstituted or substituted monovalent hydrocarbon group having 1 to 20 carbon atoms is preferred. Examples thereof include the same groups as those exemplified for the organic groups bonded to the silicon atom above (excluding alkoxy groups). Among them, a monovalent hydrocarbon group having 1 to 6 carbon atoms is preferred, and an alkyl group or an aryl group having 1 to 6 carbon atoms is more preferred. <​​​​​​​​​​​​​​ If the viscosity of component (A) is within the above range, a paste having a low initial viscosity and excellent coating properties can be easily obtained. In addition, when the paste having a low initial viscosity is a heat dissipation paste, for example, a thin paste layer can be easily formed at a predetermined location such as between a heating element and a heat dissipation component, and a paste layer that easily adheres to the target surface of the heating element or heat dissipation component can be easily formed. Therefore, the thermal resistance of the paste layer can be reduced, and electronic components with excellent heat dissipation properties can be easily obtained.

[0040] The functional group equivalent of component (A) is preferably 1000 to 50,000 g / mol, more preferably 1500 to 35,000 g / mol, from the perspectives of having a viscosity that can suppress overflow after anaerobic room-temperature thickening, not solidifying after anaerobic room-temperature thickening, and being able to easily obtain a paste that remains in a paste or rubbery state after anaerobic room-temperature thickening. The functional group of the component (A) refers to a group that reacts with free radicals generated by a redox initiator, and specifically includes a mercapto group and functional groups other than the above mercapto groups.

[0041] In addition, from the perspectives of having a viscosity that can suppress overflow after anaerobic room temperature thickening, not solidifying after anaerobic room temperature thickening, and being able to easily obtain a paste that remains in a paste or rubbery state after anaerobic room temperature thickening, it is appropriate to use, as component (A), a polysiloxane (A1) having a functional group equivalent weight preferably in the range of 1000 to 5000 g / mol, more preferably 1500 to 5000 g / mol, and a polysiloxane (A2) having a functional group equivalent weight preferably in the range of 15000 to 50000 g / mol, more preferably 20000 to 3500 g / mol. When using such polysiloxanes (A1) and (A2), the ratio of the polysiloxane (A2) to 100% by mass of the total of these polysiloxanes is preferably 50.0 to 99.5% by mass, more preferably 75.0 to 99.0% by mass.

[0042] The number average molecular weight (Mn) of component (A) as measured by gel permeation chromatography (GPC) is preferably 3,000 to 50,000, more preferably 15,000 to 25,000, from the viewpoint that a paste that can suppress overflow can be easily obtained after anaerobic room-temperature thickening despite a low initial viscosity.

[0043] From the perspective of being able to easily obtain a paste having a good balance and excellent heat resistance, low initial viscosity, and overflow suppression, when the present paste does not contain the component (D) described later, the content of the component (A) in the present paste is preferably 40.0 to 98.0 mass%, more preferably 60.0 to 95.0 mass%, relative to 100 mass% of the present paste. When the present paste contains the component (D) described below, the content of the component (A) in the present paste is preferably 5.0 to 40.0 mass%, more preferably 30.0 mass%, relative to 100 mass% of the present paste.

[0044] From the perspective of being able to easily obtain a paste having a good balance and excellent heat resistance, low initial viscosity, and overflow suppression, when the present paste contains the component (C) described later, the content of the component (A) in the present paste is preferably 40.0 to 99.0 mass %, more preferably 70.0 to 99.0 mass %, and even more preferably 85.0 to 98.5 mass % relative to 100 mass % of the total of the components (A) and (C) in the present paste.

[0045] <Redox initiator (B)> The component (B) is not particularly limited as long as it is a redox initiator, and a conventionally known redox initiator can be used. Since the component (A) having a mercapto group functions as a reducing agent, the component (B) is preferably a component (oxidizing agent) that can generate free radicals by inducing a redox reaction with the component (A). The component (B) used in the present paste may be one kind or two or more kinds.

[0046] Component (B) may, for example, be an organic peroxide, a persulfate, permanganic acid, a permanganate, manganese triacetate, cerium ammonium nitrate, cerium ammonium sulfate, bromic acid, a bromate, or hydrogen peroxide. Among these, an organic peroxide is preferred. Examples of the organic peroxide include hydroperoxides such as tert-butyl hydroperoxide, tert-amyl hydroperoxide, isopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, p-terpane hydroperoxide, and diisopropylbenzene hydroperoxide; diperoxides such as 2,5-dimethyl-2,5-di(hydroperoxide)hexane; ketones such as acetylacetone peroxide and methyl ethyl ketone peroxide; peroxyesters such as tert-butyl perbenzoate; disuccinic acid peroxide; and diglutaric acid peroxide. As the persulfate, ammonium persulfate, sodium persulfate and potassium persulfate can be exemplified. Examples of the permanganate include ammonium permanganate, alkali metal salts of permanganate (eg, potassium permanganate), and alkaline earth metal salts of permanganate. The bromate may, for example, be ammonium bromate, an alkali metal salt of bromic acid or an alkaline earth metal salt of bromic acid.

[0047] The functional group ratio represented by the following formula (1) in the present paste is preferably 1.0×10 -3 Below, more preferably 5.0×10 -4 Below, more preferably 3.0×10 -4 the following. When the present paste is made into a one-component paste, it tends to increase in viscosity during storage. However, by keeping the functional group ratio within the above range, a paste with excellent storage stability tends to be easily obtained. If the functional group ratio exceeds the above range, a paste with excellent storage stability (storage and storability) may not be easily obtained. In addition, from the viewpoint of being able to easily obtain a paste that can be anaerobic and thickened at room temperature and can suppress overflow, the functional group ratio represented by the following formula (1) in the present paste is preferably 1.0×10 -6 More than 1.0×10 -5 above. Functional group ratio = (amount of component (A) blended / functional group equivalent of component (A)) × (amount of component (B) blended / active oxygen equivalent of component (B)) (1)

[0048] In the above formula (1), the compounding amount of the component (A) is 100 parts by mass, and the compounding amount of the component (B) is the compounding amount of the component (B) relative to 100 parts by mass of the compounding amount of the component (A). Furthermore, when, for example, component (A) having a functional group equivalent of a g / mol is used at a compounding amount of x1 mass %, and component (A) having a functional group equivalent of b g / mol is used at a compounding amount of x2 mass % (where x1 + x2 = 100), "amount of component (A) compounded / functional group equivalent of component (A)" in the above formula (1) is "(x1 / a+x2 / b)". The same applies when two or more components (A) or (B) are used. The "amount of component (A)" is 100 x z / 100, for example, when a commercially available product having a purity (active ingredient amount) of z% by mass is used as component (A) with 100% by mass. The same applies to the "amount of component (B)".

[0049] The content of component (B) in the present paste is preferably an amount that satisfies the above formula (1), but from the perspectives of anaerobic viscosity increase at room temperature, suppression of overflow, and the ability to easily obtain a paste with excellent storage stability, it is preferably 0.05 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and particularly preferably 1 to 10 parts by mass relative to 100 parts by mass of component (A) in the present paste.

[0050] <Other ingredients> The present paste may further contain other components in addition to the above-mentioned components (A) and (B) as necessary, as long as the effects of the present invention are not impaired. Examples of such other components include: a compound (C) other than the above-mentioned component (A) having two or more ethylenically unsaturated bonds in one molecule; a thermally conductive filler (D); a stabilizer; a catalyst; a plasticizer such as a fluorine-based or silicone-based oil; a silane coupling agent; a surfactant; a solvent; a dispersant; a flame retardant; and a pigment. These other components may be used alone or in combination of two or more.

[0051] For example, from the viewpoint of being able to easily obtain a paste having a long pot life, the present paste preferably does not contain a platinum-based catalyst. Conventional pastes use platinum-based catalysts, but platinum-based catalysts have a short lifespan and cannot store the paste for long periods of time. Furthermore, the phrase "containing no platinum-based catalyst" means that the content of the platinum-based catalyst is, for example, 0.0001 parts by mass or less relative to 100 parts by mass of the component (A), and the lower limit is preferably 0 parts by mass.

[0052] [Compound (C) having two or more ethylenically unsaturated bonds in one molecule] The component (C) is not particularly limited as long as it is a compound having two or more ethylenically unsaturated bonds in one molecule other than the above-mentioned component (A), and a conventionally known compound (co-crosslinking agent) can be used. By using the component (C), a paste having further excellent overflow suppression properties after anaerobic viscosity increase at room temperature can be easily obtained. The component (C) used in the present paste may be one kind or two or more kinds.

[0053] The number of ethylenically unsaturated bonds in component (C) may be 2, but is preferably 3 or more, more preferably 3 to 6, from the viewpoint of being able to further suppress bleeding. The two or more ethylenically unsaturated bonds contained in the component (C) may be the same or different. That is, the component (C) may have two or more types of ethylenically unsaturated bonds.

[0054] Examples of the group having an ethylenically unsaturated bond include alkenyl groups having 2 to 8 carbon atoms, such as vinyl, methylvinyl, allyl, propenyl, isopropenyl, butenyl, pentenyl, hexenyl, and heptenyl; vinylphenyl, (meth)acryloyl, allyloxy, styryl, propargyl, and maleimide. Of these, alkenyl groups having 2 to 8 carbon atoms and (meth)acryloyl are preferred, alkenyl groups having 2 to 4 carbon atoms and (meth)acryloyl are more preferred, and vinyl and (meth)acryloyl are particularly preferred.

[0055] As component (C), there may be mentioned: polysiloxane having two or more ethylenically unsaturated bonds in one molecule; Ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, alkoxylated bisphenol A di(meth)acrylate, alkoxylated bisphenol F di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, glycerol tri(meth)acrylate ) acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol octa(meth)acrylate, ethylene oxide added trimethylolpropane tri(meth)acrylate, ethylene oxide added ditrimethylolpropane tetra(meth)acrylate, ethylene oxide added pentaerythritol tetra(meth)acrylate, ethylene oxide added diquaternary acrylate Pentaerythritol hexa(meth)acrylate, propylene oxide added trimethylolpropane tri(meth)acrylate, propylene oxide added ditrimethylolpropane tetra(meth)acrylate, propylene oxide added pentaerythritol tetra(meth)acrylate, propylene oxide added dipentaerythritol hexa(meth)acrylate, ε-caprolactone added trimethylolpropane tri(meth)acrylate, ε-caprolactone added ditrimethylolpropane tetra(meth)acrylate, ε-caprolactone added pentaerythritol tetra(meth)acrylate, Multifunctional (meth)acrylate compounds such as ε-caprolactone-added dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate succinic acid-modified products, pentaerythritol tri(meth)acrylate succinic acid-modified products, dipentaerythritol penta(meth)acrylate phthalic acid-modified products, pentaerythritol tri(meth)acrylate phthalic acid-modified products, tris((meth)acryloyloxyethyl)isocyanurate, and alkylene oxide-added tris((meth)acryloyloxyethyl)isocyanurate; Ethylene glycol divinyl ether, diethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, butanediol divinyl ether, hexanediol divinyl ether, alkoxylated bisphenol A divinyl ether, alkoxylated bisphenol F divinyl ether, trimethylolpropane trivinyl ether, ditrimethylolpropane tetravinyl ether, glycerol trivinyl ether, pentaerythritol tetravinyl ether, dipentaerythritol pentavinyl ether, dipentaerythritol hexavinyl ether, ethylene oxide-added trimethylolpropane trivinyl ether, ethylene oxide-added ditrimethylolpropane tetravinyl ether, ethylene oxide-added pentaerythritol tetravinyl ether, ethylene oxide-added dipentaerythritol hexavinyl ether and other multifunctional vinyl ethers; (Meth)acrylates containing a vinyl ether group, such as 2-vinyloxyethyl (meth)acrylate, 3-vinyloxypropyl (meth)acrylate, 1-methyl-2-vinyloxyethyl (meth)acrylate, 2-vinyloxypropyl (meth)acrylate, 4-vinyloxybutyl (meth)acrylate, 4-vinyloxycyclohexyl (meth)acrylate, 5-vinyloxypentyl (meth)acrylate, 6-vinyloxyhexyl (meth)acrylate, 4-vinyloxymethylcyclohexyl (meth)acrylate, p-vinyloxymethylphenylmethyl (meth)acrylate, 2-(vinyloxyethoxy)ethyl (meth)acrylate, and 2-(vinyloxyethoxyethoxyethoxy)ethyl (meth)acrylate; Ethylene glycol diallyl ether, diethylene glycol diallyl ether, polyethylene glycol diallyl ether, propylene glycol diallyl ether, butylene glycol diallyl ether, hexanediol diallyl ether, alkoxylated bisphenol A diallyl ether, alkoxylated bisphenol F diallyl ether, trimethylolpropane triallyl ether, ditrimethylolpropane tetraallyl ether, diallyl phthalate, glycerol triallyl ether, pentaerythritol tetraallyl ether, dipentaerythritol pentaallyl ether Polyfunctional allyl compounds such as propylene glycol ether, dipentaerythritol hexaallyl ether, ethylene oxide added trimethylolpropane triallyl ether, ethylene oxide added ditrimethylolpropane tetraallyl ether, ethylene oxide added pentaerythritol tetraallyl ether, ethylene oxide added dipentaerythritol hexaallyl ether, triallyl isocyanurate, triallyl cyanurate, triallyl formaldehyde, triallyl trimellitate, tetraallyl terephthalamide, etc. Allyl (meth)acrylates such as allyl (meth)acrylate; Multifunctional (meth)acrylamide compounds such as N,N-ethylenebis(meth)acrylamide; Polyfunctional propargyl compounds such as poly (dipropylene terephthalate); Multifunctional maleimide compounds such as N,N′-m-phenylenebismaleimide; Polyfunctional urethane (meth)acrylates obtained by reacting polyfunctional isocyanates such as toluene diisocyanate, isophorone diisocyanate, and xylene diisocyanate with hydroxyl-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; Multifunctional aromatic vinyls such as divinylbenzene.

[0056] Among them, from the perspective of being able to easily obtain a paste with excellent reactivity and excellent heat resistance, polyfunctional (meth)acrylate compounds, polyfunctional allyl compounds, and polyfunctional (meth)acrylamide compounds are preferred, polyfunctional (meth)acrylate compounds with three or more functional groups and polyfunctional allyl compounds with three or more functional groups are more preferred, and triaryl isocyanurate and trimethylolpropane tri(meth)acrylate are particularly preferred.

[0057] Examples of the polysiloxane having two or more ethylenically unsaturated bonds in one molecule include dimethylpolysiloxane terminated with dimethylvinylsiloxane at both ends of the molecular chain, dimethylpolysiloxane terminated with methylphenylvinylsiloxane at both ends of the molecular chain, dimethylsiloxane-methylphenylsiloxane copolymer terminated with dimethylvinylsiloxane at both ends of the molecular chain, dimethylsiloxane-methylvinylsiloxane copolymer terminated with dimethylvinylsiloxane at both ends of the molecular chain, dimethylsiloxane-methylvinylsiloxane copolymer terminated with silanol groups at both ends of the molecular chain, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymer terminated with silanol groups at both ends of the molecular chain, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymer terminated with silanol groups at both ends of the molecular chain, trimethylsilylalkyl terminated with dimethylsiloxane-methylvinylsiloxane copolymer, methyl(3,3,3-trifluoropropyl)polysiloxane terminated with dimethylvinylsiloxy groups at both ends of the molecular chain, and polysiloxane having the formula: (CH3)3SiO 1 / 2 The siloxane unit represented by the formula: (CH3)2(CH2=CH)SiO 1 / 2 The siloxane unit represented by the formula: CH3SiO 3 / 2 The siloxane unit represented by the formula: (CH3)2SiO 2 / 2 An organosiloxane copolymer composed of the siloxane units represented.

[0058] Specific examples of the polysiloxane having two or more ethylenically unsaturated bonds in one molecule include compounds represented by the following formula (3).

[0059]

Chemistry 2

[0060] R 3 Each independently represents an unsubstituted or substituted monovalent hydrocarbon group preferably having 1 to 10 carbon atoms. Examples thereof include the same groups as exemplified as the organic group bonded to a silicon atom and an alkenyl group. Among them, a monovalent hydrocarbon group having 1 to 6 carbon atoms is preferred, and an alkenyl group, an aryl group, and an alkyl group having 1 to 3 carbon atoms are more preferred.

[0061] As R 4 The alkyl group in can be the same linear alkyl group, branched alkyl group and cyclic alkyl group as exemplified above as the organic group bonded to a silicon atom. As R 4 The alkoxyalkyl group in the group includes groups having 2 to 10 carbon atoms, such as methoxyethyl and methoxypropyl. As R 3 and R 4 The alkenyl group in may be the same alkenyl group as exemplified as the group having an ethylenically unsaturated bond. As R 4 The acyl group in the acyl group may be a group having 2 to 10 carbon atoms, such as an acetyl group and an octanoyl group. The sum of c and d is preferably an integer of 10 to 50, and e is preferably 1.

[0062] The functional group (ethylenically unsaturated bond) equivalent weight of component (C) is preferably 4 to 25,000 g / mol, more preferably 50 to 25,000 g / mol, and even more preferably 75 to 130 g / mol, from the perspectives of having a viscosity that can suppress overflow after anaerobic room-temperature thickening, not solidifying after anaerobic room-temperature thickening, and being able to easily obtain a paste that remains in a paste or rubbery state after anaerobic room-temperature thickening.

[0063] From the perspectives of having a viscosity that can suppress overflow after anaerobic room-temperature thickening, not solidifying even after anaerobic room-temperature thickening, and being able to easily obtain a paste that remains in a paste or rubbery state even after anaerobic room-temperature thickening, component (C) preferably has a functional group ratio represented by the following formula (4) of 3 or less, more preferably 0.01 to 3, further preferably 0.01 to 2, more preferably 0.015 to 1, and particularly preferably 0.02 to 0.8. Functional group ratio = (amount of component (A) blended / functional group equivalent of component (A)) / (amount of component (C) blended / functional group equivalent of component (C)) ... (4)

[0064] In the above formula (4), the compounding amount of the component (A) is 100 parts by mass, and the compounding amount of the component (C) is the compounding amount of the component (C) relative to 100 parts by mass of the compounding amount of the component (A). Furthermore, for example, when a component (A) having a functional group equivalent of a g / mol is used at a compounding amount of x1 mass % and a component (A) having a functional group equivalent of b g / mol is used at a compounding amount of x2 mass % (where x1 + x2 = 100), "amount of component (A) compounded / functional group equivalent of component (A)" in the above formula (4) is "(x1 / a+x2 / b)". The same applies when two or more components (A) or (C) are used. The amount of component (A) is, for example, 100% by mass of a commercially available product having a purity (amount of active ingredient) of z% by mass, and the amount of component (A) is 100 × z / 100. The same applies to the amount of component (C).

[0065] The content of component (C) is preferably an amount that satisfies the above formula (4), but the content of component (C) in the present paste is preferably as low as possible. In view of this, and the fact that the paste has a viscosity that can suppress overflow after anaerobic room temperature thickening, does not solidify after anaerobic room temperature thickening, and can easily obtain a paste that remains in a paste or rubbery state after anaerobic room temperature thickening, the content of component (C) relative to 100% by mass of the present paste is preferably 0.2 to 50% by mass, more preferably 0.3 to 15% by mass, and even more preferably 0.5 to 5.5% by mass.

[0066] [Thermal conductive filler (D)] When the present paste is used as a heat dissipation paste, the present paste preferably contains component (D). When component (D) is used in the present paste, the component (D) used may be one or more. When two or more components (D) are used, two or more components (D) having different materials or different shapes, average particle sizes, etc. may be used.

[0067] As the component (D), it is preferable to use a filler having a thermal conductivity of 1 W / m·K or more. As such component (D), there may be mentioned: metal powder, metal oxide powder, metal nitride powder, metal hydroxide powder, metal oxynitride powder, metal carbide powder, carbon material, specifically: aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), beryllium oxide (BeO), zinc oxide (ZnO), silicon nitride (Si3N4), boron nitride (for example: hexagonal BN or cubic BN), aluminum nitride (AlN), silicon carbide (SiC), graphite, diamond, carbon nanotubes.

[0068] The shape of the component (D) is not particularly limited, and may be granular, scaly, or needle-shaped. However, a granular shape is preferred because it allows for higher density packing. The average particle size of the granular component (D) is, for example, 0.1 to 100 μm, preferably 0.5 to 50 μm. This average particle size is the d50 value in the particle size distribution obtained by a laser diffraction / scattering method (MICROTRAC method).

[0069] When the present paste contains component (D), the content of component (D) is preferably 30 to 80 volume % relative to 100 volume % of the present paste, more preferably 30 to 70 volume % from the viewpoints of low initial viscosity and ease of obtaining a paste with better heat dissipation properties.

[0070] Furthermore, when the paste is used as a heat dissipation material, for example, a larger amount of component (D) tends to improve thermal properties (e.g., increased thermal diffusion value and decreased thermal resistance value). Therefore, depending on the application, it may be desirable to add more component (D). However, in conventional pastes, increasing the amount of component (D) increases the initial viscosity and reduces workability (making it difficult to apply or pour the paste to a desired location). Therefore, conventional pastes cannot contain a large amount of component (D). On the other hand, since the initial viscosity of the present paste is low, by using the present paste, even if the compounding amount of the component (D) is increased, the workability is unlikely to be reduced. Therefore, according to one embodiment of the present invention, even if component (D) is added in an amount of preferably 40 to 80 volume %, more preferably 50 to 70 volume %, relative to 100 volume % of the present paste in order to obtain a paste having particularly excellent thermal properties, a paste having a low initial viscosity and excellent workability can be obtained.

[0071] [Stabilizer] The stabilizer is not particularly limited, but it is preferable to use a stabilizer that improves the storage stability of the paste. When a stabilizer is used in the present paste, the stabilizer may be used alone or in combination of two or more.

[0072] As the above-mentioned stabilizer, metal ion blocking agents and polymerization inhibitors can be mentioned. As specific examples, chelating agents such as disodium ethylenediaminetetraacetic acid dihydrate (EDTA2Na) and tetrasodium ethylenediaminetetraacetic acid tetrahydrate (EDTA4Na) can be mentioned; butylated hydroxytoluene (BHT), p-hydroxytoluene, hydroquinone (HQ), di-tert-butylhydroquinone (DTBHQ), mono-tert-butylhydroquinone (MTBHQ), 1,4-naphthoquinone, tert-butylhydroxyanisole, p-hydroxyanisole, benzoic acid, 2,5-dimethylbenzene, 1,4-naphthoquinone, tert-butylhydroxyanisole, p-hydroxyanisole, benzoic acid, 2,5-dimethylbenzene, 1,4-naphthoquinone, tert-butylhydroxyanisole, 1,4-dimethylbenzene ... -Dihydroxybenzoic acid, 2,5-dihydroxyterephthalic acid, toluic acid, catechol, tert-butylcatechol, 4-allylcatechol, 4-acetylcatechol, 2-methoxyphenol, p-methoxyphenol, 2-ethoxyphenol, 2-methoxy-4-(2-propenyl)phenol, 3,4-dihydroxybenzaldehyde, 2,3-dihydroxybenzaldehyde, benzylamine, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, tert-butylhydroxyaniline, p-hydroxyaniline, propyl gallate and other polymerization inhibitors.

[0073] When the present paste contains a stabilizer, the content of the stabilizer is preferably 0.01 to 3.0 parts by mass, more preferably 0.1 to 2.0 parts by mass, relative to 100 parts by mass of component (A), from the viewpoint of easily obtaining a paste having excellent storage stability.

[0074] [catalyst] The catalyst is not particularly limited, but a catalyst that promotes anaerobic reaction is preferably used. When a catalyst is used in the present paste, the catalysts used may be one kind or two or more kinds.

[0075] The catalyst may be a catalyst that promotes the generation of radicals from metal ions or the component (B), and a specific example thereof may be an acid or a reducing agent. Specific examples of the catalyst include saccharin, maleic acid, amine compounds, thiol compounds, and hydrazine derivatives. Examples of the amine compound include: heterocyclic secondary amines such as 1,2,3,4-tetrahydroquinoline and 1,2,3,4-tetrahydroquinoline; heterocyclic tertiary amines such as quinoline, methylquinoline, quinoxaline, and quinoxalinephenazine; aromatic tertiary amines such as N,N-dimethylanisidine, N,N-dimethylaniline, and N,N-dimethyl-p-toluidine (DMPT); aromatic secondary amines such as N,N'-1,4-phenylenebis(5-methyl-2-hexylamine); and azole compounds such as 1,2,4-triazole, oxazole, oxadiazole, thiadiazole, benzotriazole, hydroxybenzotriazole, benzothiazole, benzoxazole, 1,2,3-benzothiadiazole, and 3-mercaptobenzotriazole. Examples of the mercaptan compound include linear mercaptans such as n-dodecyl mercaptan, ethyl mercaptan, butyl mercaptan and 2-mercaptoethanol. Examples of the hydrazine derivative include methyl methylcarbamate, 1-acetyl-2-phenylhydrazine (APH), nitrophenylhydrazine (NPH) and p-trisulfonylhydrazine.

[0076] When the present paste contains a catalyst, the content of the catalyst is preferably 0.01 to 1.0 part by mass, more preferably 0.01 to 0.1 part by mass, based on 100 parts by mass of component (A), from the viewpoint of easily obtaining a paste that readily undergoes anaerobic room-temperature viscosity increase.

[0077] <Preparation Method of the Paste> The present paste can be prepared, for example, by mixing the above-mentioned components (A) and (B) and the above-mentioned other components used as necessary, and kneading and dispersing them using a stirrer, a roller, or the like.

[0078] <Physical Properties of This Paste> The initial shear viscosity (this viscosity is the initial viscosity) of this paste at 23°C measured by a cone-plate viscometer (rotation speed: 0.5 rpm) is preferably lower. Specifically, it is preferably 500 Pa·s or less, more preferably 100 Pa·s or less, particularly preferably 50 Pa·s or less, and preferably 1 Pa·s or more. If the initial viscosity of the present paste is within the above range, a paste with excellent workability (easily applied or poured to a desired location) can be readily obtained. Furthermore, when the paste having such a low initial viscosity is a heat dissipation paste, a thin paste layer can be readily formed at a desired location, such as between a heating element and a heat dissipation component, making it easier to adhere to the target surface of the heating element or heat dissipation component. This reduces the thermal resistance of the paste layer, making it easier to obtain electronic components with excellent heat dissipation properties. Generally, a paste having a low initial viscosity tends to overflow even after being thickened by heating. However, by using the paste of the present invention, overflow can be suppressed even when the paste is thickened at room temperature by anaerobic means despite having a low initial viscosity.

[0079] When 4 g of this paste is sandwiched between two copper plates at 23°C and compressed for 2.5 hours until the paste reaches a thickness of 0.4 mm, the shear viscosity of the compressed body (paste) (viscosity after anaerobic room temperature thickening) is preferably 1.5 times or more, more preferably 3 times or more, and even more preferably 10 times or more of the shear viscosity of the paste before anaerobic room temperature thickening. Furthermore, when the compressed body is rubbery, the shear viscosity (viscosity after anaerobic room temperature thickening) of the compressed body is essentially infinitely greater than the initial viscosity, and therefore, it can be said that this range is satisfied. When the ratio of the viscosity after anaerobic room-temperature thickening to the initial viscosity is within the above range, a paste having a good balance between low initial viscosity and overflow suppressability and being excellent can be easily obtained.

[0080] The viscosity after anaerobic room temperature thickening is preferably a viscosity that makes the ratio of the viscosity after anaerobic room temperature thickening to the initial viscosity within the above range, but from the perspective of being able to suppress overflow, it is specifically preferably above 20 Pa·s, more preferably above 40 Pa·s, and further preferably above 50 Pa·s. When the present paste is used for an extremely important purpose of suppressing overflow, as an example of a specific value of the viscosity after anaerobic room temperature thickening, it is preferably above 500 Pa·s, and particularly preferably above 1500 Pa·s. When the viscosity after anaerobic and room-temperature thickening is within the above range, overflow after anaerobic and room-temperature thickening can be easily suppressed by flow resistance. The viscosity after anaerobic and room-temperature thickening is specifically the viscosity measured by the method described in the Examples below.

[0081] <Application of this paste> This paste can be used without restriction for any purpose in which conventional pastes have been used. However, from the perspective of better exerting the effects of the present invention, it is suitable for use in applications where it may be exposed to high temperatures (e.g., above 200°C), applications where it is difficult to heat or irradiate the paste arranged at a specified location, and especially applications where the viscosity is required to be low when the paste is formed at a specified location by coating or pouring, and where it is required to remain in the specified location in a paste or rubber form after anaerobic viscosity increase at room temperature.

[0082] Specific examples of the above-mentioned applications include use in components such as sliding parts, brake parts, and vibration suppression and absorption parts. Furthermore, the present paste containing the above-mentioned component (D) can be used as a heat dissipation paste used between a heat generating element and a heat dissipation component such as an electronic component. This heat dissipation paste can be used as an application where the above-mentioned overflow prevention is extremely important. Furthermore, at least a portion of a member that contacts the paste (e.g., a sliding member, a brake member, a vibration suppression / absorbing member, a heating element, a heat dissipating member) (at least a portion of a portion that contacts the paste) is preferably made of metal.

[0083] In particular, the present paste containing the above-mentioned component (D) has a low initial viscosity and is inhibited from overflowing, base oil detachment, solidification, sagging, etc. after anaerobic thickening. It can maintain heat dissipation (thermal conductivity) for a long time and is therefore applicable to devices, equipment, components, etc. having a heating element. By using this paste on these objects, devices, equipment, components, etc. with excellent long-term reliability can be obtained. In particular, the paste has a low initial viscosity and good adhesion to the heating element or heat dissipation component, so a thin paste layer can be formed between the heating element and the heat dissipation component, reducing the thermal resistance generated by the paste layer, and is therefore suitable for use as a heat dissipation paste provided between the heating element and the heat dissipation component. Furthermore, since it is non-solidified, not easy to crack, and can absorb (suppress) vibration, it is suitable for use as a heat dissipation paste for vehicles such as automobiles.

[0084] As a method for forming the present paste at a prescribed position, there can be exemplified a method in which the present paste is applied to a prescribed position by a conventional coating method, or the present paste is caused to flow into a prescribed position. When the present paste is formed between two components, pressure is preferably applied after the paste is applied or flows into the paste between these components. In this case, heating can be performed as needed. For example, in the case in which the present paste is formed between a heating element and a heat dissipation component, the thickness of the formed present paste (layer) is preferably thinner, taking into account thermal resistance. Therefore, in this case, pressure is preferably applied after the paste is formed between the heating element and the heat dissipation component to extend the paste. Example

[0085] Hereinafter, the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0086] [Examples 1 to 17 and Comparative Examples 1 to 3] The anaerobic paste was prepared by mixing the respective compounding components in Table 1 at the compounding ratios shown in Table 1 (the unit of the numerical values ​​is parts by mass). Table 2 shows the details of each component in Table 1. In addition, the "functional group ratio" in Table 1 is a value calculated according to the following formula (5). For example, "E-04" means "10 -4 ”. Functional group ratio = (amount of polysiloxane blended / functional group equivalent of the polysiloxane) × (amount of initiator blended / active oxygen equivalent of the initiator) (5) [The amount of polysiloxane in formula (5) is 100 parts by mass, and the amount of initiator is the amount of initiator per 100 parts by mass of polysiloxane. When two types of polysiloxane are used, their total amount is 100 parts by mass.]

[0087] Initial viscosity The prepared anaerobic paste was allowed to stand in air at room temperature for one day to stabilize its physical properties, and then its viscosity (initial viscosity) at 23°C was measured using a cone-plate viscometer (HBDVNextCP [Brookfield]) at a rotation speed of 0.5 rpm. The results are shown in Table 1.

[0088] <Viscosity after anaerobic room temperature thickening> The prepared anaerobic paste was allowed to stand in air at room temperature for one day to stabilize its physical properties. Then, 4 g of the anaerobic paste was sandwiched between two copper plates (hard asphalt copper C1100P [made by Nickel White Co., Ltd.]) at 23°C and compressed using a gasket for 2.5 hours until the thickness of the paste reached 0.4 mm. The shear viscosity of the compressed anaerobic paste was then measured using a cone-plate viscometer (HBDVNextCP [made by Brookfield]) at a speed of 0.5 rpm. When the cone-plate viscometer was used for measurement at a speed of 0.5 rpm, if the viscosity exceeded the upper limit of the measurement, the speed was changed to 0.1 rpm for measurement. The results are shown in Table 1. In addition, even when the rotation speed was changed to 0.1 rpm, if the viscosity exceeded the upper limit of measurement, it was indicated as “>8000” in Table 1.

[0089] <Properties after anaerobic viscosity increase at room temperature> After the prepared anaerobic paste was allowed to stand at room temperature for one day to stabilize its physical properties, 4 g of the anaerobic paste was sandwiched between two copper plates (hard pitch copper C1100P [produced by Nickel White Co., Ltd.]) at 23°C and compressed using a gasket for 2.5 hours until the paste reached a thickness of 0.4 mm. This produced a compressed body. 0.2 g of the compressed body obtained using the anaerobic pastes prepared in Examples 2, 4-15, and 17 and Comparative Examples 1-3 was formed into a 5 mm square and its thickness was measured when compressed at 23°C and a pressure of 1.0 MPa. The compression conditions were as follows. In addition, for the compressed bodies obtained using the anaerobic pastes prepared in Examples 1, 3 and 16, their surface Martens hardness was measured using an ultra-microhardness tester (DUH-211 [manufactured by Shimadzu Corporation]) with a triangular pyramid indenter (edge ​​angle 115°) as the measuring indenter at a maximum test force of 0.3 mN. When the thickness of the compressed body measured using the anaerobic paste prepared in Examples 2, 4 to 15, 17 and Comparative Examples 1 to 3 was less than 200 μm, it was marked as ○ (paste-like), and when the thickness of the compressed body measured was more than 200 μm, it was marked as × (non-paste-like). In addition, for the compressed bodies obtained by using the anaerobic pastes prepared in Examples 1, 3 and 16, the surface Martens hardness was between 10 N / mm 2 The following cases are marked as ○ (rubber-like), and the surface Martens hardness of the compressed body measured is greater than 10 N / mm 2 The case of ≤ was recorded as × (cured (= non-rubbery)). The results are shown in Table 1.

[0090] Storage and Preservation The prepared anaerobic paste was allowed to stand in air at room temperature for 5 days, and then 0.2 g of the anaerobic paste was formed into a 5 mm square and its thickness was measured when it was compressed at a pressure of 1.0 MPa at 23° C. The compression conditions were as follows. The case where the measured thickness of the anaerobic paste was 200 μm or less was marked as ○ (paste-like), and the case where the measured thickness of the anaerobic paste was 200 μm or more was marked as × (non-paste-like).

[0091] Compression conditions, etc. The anaerobic paste was compressed by spreading 0.2 g of the anaerobic paste to a 5 mm square on a metal disc, clamping it with another metal disc, and tightening the screws with a torque wrench to apply a specified load to the specimen.

[0092] The thickness is measured by pre-measuring the length of the two metal discs at both ends when they are overlapped and loaded with 1 MPa (the length without the sample), and measuring the length of the two metal discs at both ends when the sample is clamped (the length with the sample), and then subtracting the length without the sample from the length with the sample. In addition, in order to take into account the change in thickness due to compression, the thickness was measured 3 minutes after compression.

[0093] The pressure was applied using a pressure sample holder (manufactured by NETZSCH Japan Co., Ltd., accessories for the Flash Analyzer LFA467) and a torque wrench. The thickness was measured using a LITEMATIC VL-50 (manufactured by Mitutoyo Co., Ltd.). A copper plate (hard pitch copper C1100P [manufactured by Nickel White Co., Ltd.]) was used as the metal disc in the anaerobic and room temperature viscosity test, and a plate made of SUS304 with a diameter of 14 mm, a thickness of 3 mm, and a surface roughness of Ra 0.2 was used in the storage and storability test.

[0094] Table 1 Table 2

Claims

1. An anaerobic paste comprising a polysiloxane having a mercapto group (A) and a redox initiator (B), It thickens under anaerobic conditions at room temperature when in contact with metal parts, and becomes paste-like or rubber-like after the thickening.

2. The anaerobic paste according to claim 1, wherein The initial shear viscosity at 23°C is below 500 Pa·s.

3. The anaerobic paste according to claim 1, wherein The functional group ratio shown in the following formula (1) is 1.0×10 -3 the following: Functional group ratio = (the amount of the polysiloxane (A) blended / the functional group equivalent of the polysiloxane (A)) × (the amount of the redox initiator (B) blended / the active oxygen equivalent of the redox initiator (B)) ... (1).

4. The anaerobic paste according to any one of claims 1 to 3, wherein Contains thermally conductive filler (D).

5. The anaerobic paste according to claim 4, wherein The content of the thermally conductive filler (D) is 30 to 80% by volume relative to 100% by volume of the anaerobic paste.

Citation Information

Patent Citations

  • Ultraviolet-viscosity-increasing-type thermo-conductive silicone grease composition

    JP2016089127A

  • Thermally conductive silicone grease composition

    JP2017075282A

  • Thermally conductive silicone putty composition

    JP2017226724A